Sport, power and culture : a social historical analysis of popular sports in Britain - Hargreaves, John. (Cambridge : Polity Press in association with Basil Blackwell, 1987)
Approaching sport and power. The repression and reform of popular sporting. Consolidating the Bourgeois model. Sport and the remaking of the working class...
Keywords: Sports; Great Britain; Social aspects; Power (Social sciences); Sports -- Social aspects -- Great Britain; Sports -- Great Britain -- History; Social classes -- Great Britain